Chloroplast Chaperonin: An Intricate Protein Folding Machine for Photosynthesis - Zhao, Qian; Liu, Cuimin (Frontiers in Molecular Biosciences, 2018)
Group I chaperonins are large cylindrical-shaped nano-machines that function as a central hub in the protein quality control system in bacterial cytosol, mitochondria and chloroplasts. In chloroplasts, proteins newly synthesized by chloroplast ribosomes, unfolded by diverse stresses, or transmembrane transported from the cytosol run the risk of aberrant folding and aggregation. The chloroplast chaperonin system assists these proteins in folding into their native states. A widely known protein folded by chloroplast chaperonin is the large subunit of ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco), an enzyme responsible for the fixation of inorganic CO2 into organic carbohydrates during photosynthesis. Chloroplast chaperonin was initially identified as a Rubisco-binding protein. Unlike their homo-oligomer homologues from bacteria and mitochondria, chloroplast chaperonin complexes exist as more intricate hetero-oligomers since all photosynthetic eukaryotes encode multiple chaperonin genes in their genomes which can be divided into α and β types. Group I chaperonin requires proper interaction with a detachable lid-like co-chaperonin in the presence of ATP and Mg2+ for substrate encapsulation and conformational transition. Besides typical Cpn10-like co-chaperonin, a unique co-chaperonin consisting of two tandem Cpn10-like domains joined head-to-tail exists in chloroplasts. Since chloroplasts were proposed as sensors to various environmental stresses, this diversified chaperonin system has the potential to adapt to more complex situations by accommodating specific substrates or increasing the possibility for regulation on both transcriptional and post-translational levels. In this review, we discuss recent progress on the unique structure and function of the chloroplast chaperonin system based on model organisms Chlamydomonas reinhardtii and Arabidopsis thaliana. Knowledge of the chloroplast chaperonin system may ultimately lead to successful reconstitution of eukaryotic Rubisco in vitro.